2006
DOI: 10.1093/aje/kwj097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium Supplementation on Cardiovascular Disease Incidence and Mortality: Secondary Analyses in a Randomized Clinical Trial

Abstract: Despite the documented antioxidant and chemopreventive properties of selenium, studies of selenium intake and supplementation and cardiovascular disease have yielded inconsistent findings. The authors examined the effect of selenium supplementation (200 microg daily) on cardiovascular disease incidence and mortality through the entire blinded phase of the Nutritional Prevention of Cancer Trial (1983-1996) among participants who were free of cardiovascular disease at baseline (randomized to selenium: n = 504; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(97 citation statements)
references
References 26 publications
6
87
2
2
Order By: Relevance
“…In the Health Professionals Follow-Up Study, selenium levels were inversely associated with risk of nonfatal myocardial infarction but not fatal coronary heart disease (18). A secondary analysis of the Nutritional Prevention of Cancer Trial showed that selenium supplementation (200 µg/day) was not associated with cardiovascular disease outcomes (19). The heterogeneity among studies may be due to the differences in selenium levels in the populations studied, as the selenium content of plant and animal foods is usually related to the local selenium content of the soil.…”
Section: Discussionmentioning
confidence: 99%
“…In the Health Professionals Follow-Up Study, selenium levels were inversely associated with risk of nonfatal myocardial infarction but not fatal coronary heart disease (18). A secondary analysis of the Nutritional Prevention of Cancer Trial showed that selenium supplementation (200 µg/day) was not associated with cardiovascular disease outcomes (19). The heterogeneity among studies may be due to the differences in selenium levels in the populations studied, as the selenium content of plant and animal foods is usually related to the local selenium content of the soil.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports regarding the effectiveness of intervention with selenium on cardiovascular disease [27][28][29][30][31].…”
Section: Selenium and Cardiovascular Diseases: From Prevention To Carmentioning
confidence: 99%
“…Selenium improves sperm motility and hence human reproduction (Hawkes and Turek, 2001). It is also an essential co-factor of antioxidant enzyme such as glutathione peroxidase (Zhang et al, 1999) and its deficiency has been associated with cardiovascular diseases, diabetes, arthritis (Stranges et al, 2006;Coppinger and Diamond, 2001). It has also been shown to have protective role against cancers such as prostrate (Bjelakovic et al, 2004;Yu et al, 1997) and to improve immune function (Broome et al, 2004).…”
Section: Resultsmentioning
confidence: 99%